Lubricin is Required for the Structural Integrity and Post-natal Maintenance of TMJ. (July 2014) - Koyama, E.; Saunders, C.; Salhab, I.; Decker, R.S.; Chen, I.; Um, H.; Pacifici, M.; Nah, H.D.
The Proteoglycan 4 (Prg4) product lubricin plays essential roles in boundary lubrication and movement in limb synovial joints, but its roles in temporomandibular joint (TMJ) are unclear. Thus, we characterized the TMJ phenotype in wild-type and Prg4 –/– mouse littermates over age. As early as 2 weeks of age, mutant mice exhibited hyperplasia in the glenoid fossa articular cartilage, articular disc, and synovial membrane. By 1 month of age, there were fewer condylar superficial tenascin-C/Col1- positive cells and more numerous apoptotic condylar apical cells, while chondroprogenitors displayed higher mitotic activity, and Sox9-, Col2-, and ColX- expressing chondrocyte zones were significantly expanded. Mutant subchondral bone contained numerous Catepsin K - expressing osteoclasts at the chondro-osseous junction, increased invasive marrow cavities, and suboptimal subchondral bone. Mutant glenoid fossa, disc, synovial cells, and condyles displayed higher Hyaluronan synthase 2 expression. Mutant discs also lost their characteristic concave shape, exhibited ectopic chondrocyte differentiation, and occasionally adhered to condylar surfaces. A fibrinoid substance of unclear origin often covered the condylar surface. By 6 months of age, mutant condyles displayed osteoarthritic degradation with apical/mid-zone separation. In sum, lubricin exerts multiple essential direct and indirect roles to preserve TMJ structural and cellular integrity over post-natal life.